2017
DOI: 10.1007/s00259-017-3770-9
|View full text |Cite
|
Sign up to set email alerts
|

[18F]FDG PET/CT features for the molecular characterization of primary breast tumors

Abstract: Our results suggest a complementary role of standard PET imaging parameters and advanced imaging features for the in vivo biological characterization of BC lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 43 publications
3
50
1
2
Order By: Relevance
“…Key to this discrepancy seems to be the partial volume effect. Similar to our study, Antunovic et al performed partial volume correction on their metric SUV data and similarly missed an association of size and metabolism [48]. We believe partial volume correction is a crucial feature which is not discussed broadly enough, but is essential for future studies and clinically relevant for therapy monitoring [49].…”
Section: Discussionsupporting
confidence: 80%
“…Key to this discrepancy seems to be the partial volume effect. Similar to our study, Antunovic et al performed partial volume correction on their metric SUV data and similarly missed an association of size and metabolism [48]. We believe partial volume correction is a crucial feature which is not discussed broadly enough, but is essential for future studies and clinically relevant for therapy monitoring [49].…”
Section: Discussionsupporting
confidence: 80%
“…In some breast cancer subtypes (luminal A), FDG uptake is physiologically influenced by both the features of the tumor and hormonal fluctuations during the menstrual cycle (15). In addition to the FDG uptake value, advanced imaging features such as histogram of FDG-PET can be used to separate molecular and histological subtypes (16,17). It has also been reported that FDG-PET radiomics are associated with various tumor aspects (namely, Ki67, pCR after NAC and risk of recurrence) and may potentially become unique pretreatment biomarkers of diagnosis and prognosis (18).…”
Section: Fluorodeoxyglucose Pet and Tumor Biologymentioning
confidence: 99%
“…Additionally, PET/ CT is clinically indicated only for stage III breast cancer patients and so stage I and II breast cancers, which represent the majority, have been excluded from the analysis of these retrospective datasets. Radiogenomic analyses to date have principally focused on metabolic activity parameters of the primary tumor, most commonly via analysis of the maximum standardized uptake values, but also via analysis of the metabolic tumor volume and total lesion glycolysis (30)(31)(32)(33)(34)(35)(36)(37)(38)(39). While more advanced metrics such as histogram-based features have only recently been explored (30).…”
Section: Fdg Pet/ctmentioning
confidence: 99%